SUFISTIC NAHW PEDAGOGY: INTEGRATING ARABIC GRAMMAR AND TASAWWUF IN MORAL EDUCATION IN PESANTREN - Rohman, Abdul; Maksum, Ali; Wargadinata, Wildana; Taufiq, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study addresses the epistemological gap between exoteric knowledge (‘ilm al-lisān) and esoteric knowledge (‘ilm al-qalb) in pesantren education, which often results in a dichotomy between linguistic competence and ethical conduct. The study offers a new pedagogical model by integrating Sufistic elements into Nahw (Arabic grammar) education, thus contributing to the moral and spiritual formation of students. Using a qualitative approach with an Interpretive Phenomenological Analysis (IPA) design at Pesantren Babussalam Pagelaran, data were collected through in-depth interviews and participant observation with teachers and senior students. The findings reveal that Sufistic Nahw pedagogy transforms Nahw from a mere linguistic tool into a medium for tazkiyat al-nafs. By reviving symbolic interpretations of grammatical structures within the Sufi tradition and applying the takhallī–taḥallī–tajallī framework, this integration effectively fosters moral awareness, modesty (al-ḥayā’), and self-control among students. This research provides a significant pedagogical innovation by positioning linguistic education as a core component of spiritual development in Islamic educational institutions.